Manual de traccion animal - Sotto Batista, Pedro; Wong Barreiro, Mayra; Martínez Cañizares, José. A. (La Habana (Cuba), 1996)
(Es)
Ilus.
Keywords: TRACCION ANIMAL; ANIMALES DE TIRO; MANEJO DEL GANADO; CUBA